Size-dependent effects of ZnO nanoparticles on performance, microbial enzymatic activity and extracellular polymeric substances in sequencing batch reactor. (February 2020) - Wang, Sen; Gao, Mengchun; Ma, Bingrui; Xi, Min; Kong, Fanlong
Abstract: ZnO nanoparticles (NPs) have been detected in various wastewater treatment plants. It is widely assumed that size has a crucial effect on the NPs toxicity. Concerns have been raised over probable size-dependent toxicity of ZnO NPs to activated sludge, which could eventually affect the treatment efficiencies of wastewater treatment facilities. The size-dependent influences of ZnO NPs on performance, microbial activities, and extracellular polymeric substances (EPS) from activated sludge were examined in sequencing batch reactor (SBR) in present study. Three different sizes (15, 50, and 90 nm) and five concentrations (2, 5, 10, 30, and 60 mg L −1 ) were trialled. The inhibitions on COD and nitrogen removal were determined by the particle size, and smaller ZnO NPs (15 nm) showed higher inhibition effect than those of 50 and 90 nm, whereas the ZnO NPs with size of 50 nm showed maximum inhibition effect on phosphorus removal among three sizes of ZnO NPs. After exposure to different sized ZnO NPs, microbial enzymatic activities and removal rates of activated sludge represented the same trend, consistent with the nitrogen and phosphorus removal efficiency. In addition, apparent size- and concentration-dependent effects on EPS contents and components were also observed. Compared with the absence of ZnO NPs, 60 mg L −1 ZnO NPs with sizes of 15, 50, and 90 nm increased the EPS contents from 92.5, 92.4, and 92.0 mg g −1 VSS to 277.5, 196.8, and 178.2 mg g −1 VSS ( p  < 0.05), respectively. The protein and polysaccharide contents increased with the decreasing particle sizes and increasing ZnO NPs concentrations, and the content of protein was always higher than that of polysaccharide. Graphical abstract: Image 1 Highlights: Size-dependent effects of ZnO NPs on the performance of SBR were studied. ZnO NPs had size- and concentration-dependent effects on COD and N removal. The ZnO NPs of 50 nm showed maximum inhibition effect on P removal. EPS contents increased in size- and concentration-dependent manner. Abstract : ZnO NPs exhibited size-dependent effects on the inhibition on COD and nitrogen removal, as well as the production of EPS.